Using adaptive traffic lights for improvement of environmental situaiton at metropolis crossroads - Galchenko, G.A.; Byrnysheva, M.V.; Drozdov, D.S. (Bezopasnostʹ tehnogennyh i prirodnyh sistem, 2020)
Introduction. Jams at crossroads lead to emissions in atmosphere of great volumes of pollutants. The problem of unloading of a transport artery can be decided partially by means of usage of an adaptive mode of switching of a light signal. The analysis of a transport situation should be executed previously by means of various means and program complexes.Problem statement. The task of the given research is the analysis of a transport situation at crossroads of Rostov-on-Don on the basis of full-scale supervision and theoretical calculations, development of advisories on the enhancement of organisation of traffic.Theoretical part. The main mathematical method on which basis the computer program is developed, the method of electrodynamic modelling is. The analysis of the given full-scale supervision, theoretical calculations and presentposition sensors of availability of the car is carried out.Conclusions. Full-scale supervision and mathematical calculations showed significant degree of intensity of traffic on the given crossroads. Installation of an adaptive light signal will promote improvement of a transport situation. For realisation of an adaptive mode of switching of a light signal it is offered to use TrafiCam - the sensor of availability of the car.